Ayurvedic Management of Pancreatitis (International Journal of Ayurveda and Pharma Research, 2024)
Pancreatitis is the life threatening metabolic pathology of the gastrointestinal system. It progressively damages the pancreas and result in the loss of its functions. The prevalence rate of pancreatitis in India is 7.9 per 10, 0000. For male and female respectively 8.6 and 8 in India. With overall 10 year and 20 year survival rates are estimated to be about 70% to 45% respectively. In the contemporary science the treatment protocol is limited to painkillers, intravenous fluids and pancreatic enzymes. Despite of advance techniques in the allopathic science the prognosis of the disease is unclear. Ayurvedic formulations of mineral complex including a diet and moderate rest have shown excellent result. In this case report a 40 year old male patient a known case of chronic pancreatitis with recurrent abdominal pain which radiates to back, nausea, vomiting, tenderness, anorexia, along with elevated serum amylase level was managed effectively with Ayurvedic medications by the Department of PG Study in Shalyatantra OPD Dr. BRKR Government Ayurvedic Medical College and Hospital, Hyderabad. In Ayurveda this condition can be correlated Agnashayashoth which comes under Pittodara. And it was successfully treated with the medications like Shankha vati, Kravyadi ras, Arogyavardgani vati. Within 4 months of treatment patient become normal. There was no pain abdomen, nausea, vomiting, bloating of abdomen. And serum amylase came to its normal level. This shows that Ayurvedic herbo mineral formulations showing promising result in the management of pancreatitis.